Haemodynamic instability of uncommon aetiology in Switzerland. (18th March 2016) - Pucci, Lorenzo; Addor, Orane; Duplain, Hervé
Abstract : In Switzerland, vitamin C deficiency is a rare condition. Nonetheless, in clinical practice, there are some patients exhibiting a vitamin C deficiency as a result of an unbalanced diet or intestinal malabsorption. We report the clinical history of a 55-year-old man known for alcoholism and insufficient intake of fresh fruits and vegetables. He was admitted to the intensive care unit, for haemodynamic instability caused by blood loss due to fragile vessels (skin, gastrointestinal). Further analyses revealed a severe lack of vitamin C. The patient received a high dose of intravenous substitutive treatment, leading to a favourable clinical outcome.